Lachninae collected in Valtellina (ltaly) by suction trap and record of a new species far the ltalian fauna (Homoptera Aphididae ) (Bollettino di zoologia agraria e bachicoltura, 2024)
In 1992 and 1993 a Rothamsted type suction trap was used in Valtellina (Sondrioprovince -1) to collect aphids. The trap worked from April to November. In thefirst year 61 specimens were catched, belonging to 22 species, during the secondyear 133 individuals were collected belonging to 15 species. Tue total number ofspecies was 27. Trama (Trama) rara Mordvilko is recorded for the first time forItaly.
Keywords: Aphididae Lachninae; suction trap; Valtellina; Italy